Springer Handbook of Computational Intelligence 2015
DOI: 10.1007/978-3-662-43505-2_51
|View full text |Cite
|
Sign up to set email alerts
|

Many-Objective Problems: Challenges and Methods

Abstract: This chapter presents a short review of the stateof-the-art efforts for understanding and solving problems with a large number of objectives (usually known as many-objective optimization problems, MOP s). The first part of the chapter presents the current studies aimed at discovering the sources that make a multiobjective optimization problem (MOP) harder when more objectives are added, degrading in this way, the performance of a multiobjective evolutionary algorithm (MOEA). Next, some of the most relevant tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Multi-objective optimization problems involve optimizing multiple objectives simultaneously [26]. Various goals often interact with each other, and these interactions can be classified as conflicts and harmony [27]. Conflicting relationships mean that as a goal improves, the other worsens, and harmony means that as a goal improves, the other also improves.…”
Section: Definition Of a Multi-objective Problemmentioning
confidence: 99%
“…Multi-objective optimization problems involve optimizing multiple objectives simultaneously [26]. Various goals often interact with each other, and these interactions can be classified as conflicts and harmony [27]. Conflicting relationships mean that as a goal improves, the other worsens, and harmony means that as a goal improves, the other also improves.…”
Section: Definition Of a Multi-objective Problemmentioning
confidence: 99%
“…Simultaneously optimizing many (more than three) quality criteria is a challenging task, requiring further studies on existing many-objective optimization techniques to cope with this goal. For example, when more objectives are considered, selecting appropriate individuals for the next generation that can help the population toward the Pareto optimal set is very difficult [115]. Despite some recent success in tackling this issue in EC-based algorithms, we cannot simply use these algorithms because proper modifications are needed to cope better with our problem.…”
Section: Many-objective Optimisationmentioning
confidence: 99%
“…The so-called dominant resistance solution is a type of special solution that takes extremely poor values on at least one objective, while achieving (approximately) optimal values on the remaining other objectives. Many studies have shown that as the number of objectives increases, the number of DRSs shows an upward trend [31], which exacerbates the adverse impact of ADP on algorithm convergence. The consequence is that the final solution may be widely distributed in the objective space, but far from the desired PF.…”
Section: Introductionmentioning
confidence: 99%